Home, identity and belonging in Nunavut: In conversation with Rachel Michael - McCartney, Shelagh (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2026)
This special issue is strengthened by the perspective of Rachel Michael, an emerging Inuk leader whose work bridges youth advocacy, community wellbeing, and the urgent realities of housing and homelessness in Nunavut. Raised in Iqaluit and deeply rooted in Inuit cultural life, Michael brings a lived understanding of how home, identity, and belonging are shaped by both cultural continuity and colonial pressures. Her experience spans mental health support, community literacy, child and youth protection, and housing and homelessness—fields that collectively reveal how the social fabric of Inuit communities is impacted by unstable or inadequate housing. Michael's insights foreground the ways housing intersects with the lives of Inuit youth, families, and caregivers, illuminating how overcrowding, displacement, and homelessness echo into mental health, safety, and community cohesion. She speaks from the vantage point of someone who has worked directly with those most affected—youth navigating care systems, families without stable shelter, and community members facing the compounded effects of poverty and colonization. In her work, housing emerges not simply as a matter of infrastructure, but as a determinant of wellness, cultural continuity, and the ability of Inuit to thrive in their homelands. In preparing this piece, Michael and Shelagh McCartney discussed the importance of Inuit-led planning, design, governance, and service delivery that reflect Inuit values and visions for the future. Her voice reminds us that the future of northern housing is inseparable from the wellbeing of Inuit youth and families, and that meaningful progress depends on supporting Inuit leadership at all levels.